Tumor-Stroma Interaction in PDAC as a New Approach for Liquid Biopsy and its Potential Clinical Implications - Götze, Julian; Nitschke, Christine; Uzunoglu, Faik G.; Pantel, Klaus; Sinn, Marianne; Wikman, Harriet (Frontiers in Cell and Developmental Biology, 2022)
The extremely poor prognosis for patients with pancreatic ductal adenocarcinoma (PDAC) has remained unchanged for decades. As a hallmark of PDAC histology, the distinct desmoplastic response in the tumor microenvironment is considered a key factor exerting pro- and antitumor effects. Increasing emphasis has been placed on cancer-associated fibroblasts (CAFs), whose heterogeneity and functional diversity is reflected in the numerous subtypes. The myofibroblastic CAFs (myCAFs), inflammatory CAFs (iCAFs) and antigen presenting CAFs (apCAFs) are functionally divergent CAF subtypes with tumor promoting as well as repressing effects. Precise knowledge of the underlying interactions is the basis for a variety of treatment approaches, which are subsumed under the term antistromal therapy. Clinical implementation is still pending due to the lack of benefit – as well as paradoxical preclinical findings. While the prominent significance of CAFs in the immediate environment of the tumor is becoming clear, less is known about the circulating (c)CAFs. cCAFs are of particular interest as they seem not only to be potential new liquid biopsy biomarkers but also to support the survival of circulating tumor cells (CTC) in the bloodstream. In PDAC, CTCs correlate with an unfavorable outcome and can also be employed to monitor treatment response, but the current clinical relevance is limited. In this review, we discuss CTCs, cCAFs, secretomes that include EVs or fragments of collagen turnover as liquid biopsy biomarkers, and clinical approaches to target tumor stroma in PDAC.